Akulturasi Budaya dalam Tari Gambang Semarang - Opsantini, Rista Dewi; Septiyan, Dadang Dwi (MATRA: Jurnal Seni Musik Tari Teater & Rupa, 2023)
The Gambang Semarang Dance was born and developed in the 1940s in the form of musical arts, vocal arts, comedy arts and dance arts. The problems that arise are about how the Gambang Semarang exists and what characteristics it has as a cultural heritage that distinguishes it from the Gambang Semarang modification of artist creativity. Gambang Semarang is a performing art resulting from the acculturation of Javanese and Chinese arts. This study aims to describe cultural acculturation in the Gambang Semarang Dance in Semarang City. This research uses qualitative methods and the data obtained is through observation and literature study. The results of the study show that the motion of the Gambang Semarang Dance symbolizes the blend of Chinese and Indonesian culture. The distinctive feature of this dance movement lies in the movement of the soles of the feet which tiptoe according to the rhythm of the song which is agile and dynamic.